OPTIMIZING RETURN OF HAJJ FUND MANAGEMENT AGENCY WITH STRATEGIC ASSET ALLOCATION - Qohar Syakir, Ahmad
Hajj Operation Fees (BPIH) consist of Direct and Indirect Costs. Direct costs from initial deposit and full payment of prospective pilgrims to Hajj, while indirect costs come from the value of developing the initial deposit funds for prospective pilgrims. Value The benefits of developing funds in the last 5 years, 2014 - 2018, have not been maximized and have not been able to meet the target value of placement and investment instruments that still contain deposits and sukuk. Based on historical returns in 2014 - 2018, an average ROI of 4.65% was obtained with a standard deviation risk of 0.68%. Capital Market and the application of tax saving strategies, Held To Maturity (HTM) and Available For Sale (AFS) allocation strategies in debt securities, and asset liability management strategies. From the comparison of portfolio construction conducted using the Markowitz method using Microsoft Excel Solver, the benefit value obtained is better than historical data, namely the variation of investment instruments and the weight that has been processed. Based on the Hajj Financial Management Agency (BPKH), it is necessary to apply the Strategic Asset Allocation based on the Markowitz method to obtain optimal profits.